STUDIES ON THE SPAWNING BIOLOGY OF THE TRENCHED SARDINE, SARDINELLA SIRM (WALBAUM), FROM VIZHINJAM, SOUTH-WEST COAST OF INDIA - Lazarus, S (Indian Journal of Fisheries, 2011)
Development of ova to maturity and the duration and frequency of spawning indicated that Sardinellasirm would spawn not only in spurts but also nonsynchronically. Presence of more than two distinctbatches of ova in the ovaries indicated that the fish spawns twice in a season. The spawning season extendedfrom December to February off Vizhinjam. Females attained maturity at a larger size than males.The minimum size at first maturity was found to be 175-179 mm for males and 180 -184 mm for females.The overall sex-ratio was unequal and females predominated from 105 mm size onwards. Fecundityshowed a wide range of variation from 21.5 to 132.9 thousands. The spawning migration of the fish towardsthe inshore waters off Vizhinjam was observed